2022
DOI: 10.1101/2022.07.12.499660
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tejas functions as a core component of nuage assembly and precursor processing inDrosophilapiRNA biogenesis

Abstract: Piwi-interacting RNAs (piRNAs), a class of 23- to 29-nt gonad-specific small RNAs, function to combat transposons in gonads. piRNAs are thought to be processed and amplified in membrane-less granules called nuage in germline cells. In Drosophila, two PIWI family proteins, several Tudor-domain containing (Tdrd) proteins and RNA helicases are assembled at perinuclear region of germline cells, forming nuage to process into piRNAs. Among those, Tejas (Tej), a fly homolog of mouse Tdrd5, has been known as a robust … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 86 publications
2
2
0
Order By: Relevance
“…Instead, we discovered that the Tejas – Krimper complex may provide a direct link between Vasa and Aub. Together with our and recent data (Lin et al 2023) on the Tejas-Spindle E interaction, we conclude that Tejas is a critical core component of nuage.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Instead, we discovered that the Tejas – Krimper complex may provide a direct link between Vasa and Aub. Together with our and recent data (Lin et al 2023) on the Tejas-Spindle E interaction, we conclude that Tejas is a critical core component of nuage.…”
Section: Discussionsupporting
confidence: 87%
“…Tejas has also been suggested to associate with the TDRDs Tapas ( Drosophila ortholog of TDRD7) and Spindle E (a.k.a. Homeless; Drosophila ortholog of TDRD9) (Patil and Kai 2010; Patil et al 2014; Lin et al 2023), and we confirmed Tapas ( Figure 1B, Supplementary Figure 2P ) and Spindle E as Tejas binding partners ( Figures 1B and 5B, Supplementary Figure 2 ). Because we did not obtain a high confidence structural model for the Tejas - Tapas complex, we did not further characterize this interaction.…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations